Protection against duck hepatitis a virus type 1 conferred by a recombinant avian adeno-associated virus. (21st July 2018) - Wang, A P; Liu, L; Gu, L L; Guo, C M; Wu, S; Feng, Q; Xia, W L; Wu, Z; Zhu, S Y
ABSTRACT: The avian adeno-associated virus (AAAV) has been proved to be an efficient gene transfer vector for human gene therapy and vaccine research. In this experiment, an AAAV-based vaccine was evaluated for the development of a vaccine against duck hepatitis a virus type 1 (DHAV-1). The major capsid VP1 gene was amplified and subcloned into pFBGFP containing the inverted terminal repeats of AAAV, and then the recombinant baculovirus rBac-VP1 was generated. The recombinant AAAV expressing the VP1 protein (rAAAV-VP1) was produced by co-infecting Sf9 cells with rBac-VP1 and the other 2 baculoviruses containing AAAV functional genes and structural genes respectively, and confirmed by electron microscopy, Western blotting and immunofluorescence assays. Quantitative real-time PCR revealed that the titer of rAAAV-VP1 was about 9 × 10 12 VG/mL. Immunogenicity was studied in ducklings. One day ducklings were injected intramuscularly once with rAAAV-VP1. Serum from rAAAV-VP1-vaccinated ducklings showed a systemic immune response evidenced by VP1-specific enzyme-linked immunosorbent assay and virus neutralization test. Furthermore, all ducklings inoculated with rAAAV-VP1 were protected against DHAV-1 challenge. The data of quantitative real-time RT-PCR from livers of challenged ducklings also showed that the level of virus copies in rAAAV-VP1 group was significantly lower than that of the PBS group. Collectively, these results demonstrate that the AAAV-based vaccine is a potential vaccine candidate for the control of duck viral hepatitis.